1981
DOI: 10.1007/bf00014029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH, phosphate and ammonia on the rate of uptake of nitrate and ammonia by freshwater phytoplankton

Abstract: The effect of phosphate (PO4 + 3 ) and pH in regulating nitrate (NO 3 ) and ammonia (NH 3 ) uptake by phytoplankton was investigated in two Oklahoma lakes using 1 N tracers. Addition of PO4+ 3 above ambient concentrations had a negligible effect on the rate of uptake of NO or NH3 + . Manipulation of pH of lake water had little effect on uptake of either N0 3 or NH3+. A correlation analysis suggested that NO3-is not used by phytoplankton when NH3 + concentrations exceed about 210 pg NH3+-N(1) -'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Concerning nitrate, the lack of impact of seawater acidification alone is similar to the response reported for freshwater phytoplankton [89] , for pH T s ranging between 6.6 and 9.2. Conversely, in some marine macroalgae, some authors [90] [92] observed an enhancement of nitrate uptake at high CO 2 levels due to an increase in the activity of the nitrate reductase.…”
Section: Discussionsupporting
confidence: 81%
“…Concerning nitrate, the lack of impact of seawater acidification alone is similar to the response reported for freshwater phytoplankton [89] , for pH T s ranging between 6.6 and 9.2. Conversely, in some marine macroalgae, some authors [90] [92] observed an enhancement of nitrate uptake at high CO 2 levels due to an increase in the activity of the nitrate reductase.…”
Section: Discussionsupporting
confidence: 81%
“…The threshold for the effect of ammonium on nitrate uptake is quite variable, ranging in cultures from 0.1 to 90 LIM (Table 5 ) , and in the field from 0.1 to 15 CIM (Kuenzler et al 1979, Toetz 1981, Paasche & Kristiansen 1982, Berman et al 1984, Prjscu & Priscu 1984, Probyn 1985, Lipschultz et al 1986, Queguiner et al 1986, Pennock 1987. Considerable variation would be expected in thresholds because they probably result from a number of interacting biochemical processes (but the cause is currently unknown) and they are defined differently in various studies.…”
Section: Analysis Of Existing Data On Inhibitionmentioning
confidence: 99%
“…Limnological knowledge and their proper applications for better fish yield and management of the ecosystems are prerequisites to sustainable fish sectoral development and maintenance of the eutrophic nature of the wetland ecosystem (Wetzel 1983). Fish health and management of other biodiversity are practical applications of limnology and aquacultural environment (Khan andChowdhury 1974 andToetz 1971). It is most important to study the interrelationship between the physico-chemical aspects and between phyto-zooplankton and the effect of agricultural effluent on the biota.…”
Section: Introductionmentioning
confidence: 99%